Neonatal lung ultrasound in the UK: A framework for practice - Virginie Meau-Petit; Mahmoud Montasser; Anna Milan (Global Pediatrics, 2023)
Lung ultrasound (LU) is a tool routinely used in adult and paediatric practice, and its application is gradually expanding to support the management of newborn infants. LU has the potential to improve the ability of clinicians to promptly and accurately identify respiratory conditions affecting the neonate and can guide appropriate treatment. While its role in neonatology is supported by growing international evidence, its routine use is not fully established in the UK. Point-of-care ultrasound (POCUS), which includes LU, has however already been incorporated in undergraduate medical curricula in some countries, and doctors in training are expressing growing interest in the subject. Transition to incorporating LU in routine practice requires appropriate time and planning, and UK neonatal units will need to build experience and confidence in this tool.On the behalf of the neoFOCUS-UK group, we present a framework for practice, including a full protocol and a standardised electronic LU report, that we hope will be of use for neonatal units in the UK interested in the implementation of neonatal LU.